Class size effects: Evidence using a new estimation technique - Kevin Denny; Veruska Oppedisano (University College Dublin, UCD School of Economics, 2010)
This paper estimates the marginal effect of class size on educational attainment of high school students. We control for the potential endogeneity of class size in two ways using a conventional instrumental variable approach, based on changes in cohort size, and an alternative method where identification is based on restriction on higher moments. The data is drawn from the Program for International Student Assessment (PISA) collected in 2003 for the United States and the United Kingdom. Using either method or the two in conjunction leads to the conclusion that increases in class size lead to improvements in student's mathematics scores. Only the results for the United Kingdom are statistically significant.
Keywords: 330; class sizes; educational production